2021
DOI: 10.3390/su131810412
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Action of Three Piper Plant Extracts and Biofertilizer for Growth Promotion and Biocontrol of Blast Disease in Red Rice

Abstract: Bali is a world tourist destination and has many natural resources that need to be developed to support the tourism sector. One of the local Bali resources that has the potential to be developed to support tourism and food is the local red Bali rice. This local Balinese rice is a characteristic of the ecotourism area of the Jatiluwih village of Tabanan, Bali. Balinese rice is grown with inorganic pesticides and there is an urgent need to develop organic pesticides as a sustainable approach to rice farming. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Several plant species explored for natural compounds that are effective against phytopathogenic fungi [ 16 ]. Recently, many studies with some modifications revealed that plant extracts along with PGPR have been considered the utmost strategy for the management and control of diseases [ 17 , 18 ]. Ginger ( Zingiber officinale ) show antifungal activity against various microbes due to the presence of monoterpenoids, sesquiterpenoids, phenolic compounds, and its derivatives, aldehydes, ketones, alcohols, esters, which make it an interesting alternative to synthetic antimicrobials [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several plant species explored for natural compounds that are effective against phytopathogenic fungi [ 16 ]. Recently, many studies with some modifications revealed that plant extracts along with PGPR have been considered the utmost strategy for the management and control of diseases [ 17 , 18 ]. Ginger ( Zingiber officinale ) show antifungal activity against various microbes due to the presence of monoterpenoids, sesquiterpenoids, phenolic compounds, and its derivatives, aldehydes, ketones, alcohols, esters, which make it an interesting alternative to synthetic antimicrobials [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several plant species explored for natural compounds that are effective against phytopathogenic fungi 15 . Recently, many studies with some modi cations revealed that plant extracts along with PGPR have been considered the utmost strategy for the management and control of diseases 16,17 . Further, investigation and evaluation of bene cial PGPR strains along with some plant extracts, composting, and biochar amendments are used to enhance soil fertility and suppressed the pathogenic mechanism 2 , despite all PGPR being useful for the enhancement of crop yield and improvement both qualitatively and quantitatively, respectively 4,18 .…”
Section: Introductionmentioning
confidence: 99%